Case report: Successful treatment with the combined therapy of interferon-alpha 2b and anlotinib in a patient with advanced hepatic epithelioid hemangioendothelioma - Liu, Xiaolei; Zhou, Ruiquan; Si, Shuang; Liu, Liguo; Yang, Shiwei; Han, Dongdong; Tan, Haidong (Frontiers in Medicine, 2022)
Hepatic epithelioid hemangioendothelioma (HEH) is a very rare tumor originated from vascular endothelial cells, with unpredictable malignancy. Currently, there is no standard treatment protocol established yet. Both surgical resection and liver transplantation have been reported to be effective treatments for HEH, however multiple intrahepatic lesions or extrahepatic metastasis makes these procedures unsuitable to most patients. Systematic therapy has also been investigated, but the results are undetermined due to the limited cases. Interferon-alpha 2b (IFN-a 2b) has also been used for the treatment of HEH. Based on our previous study, the rate of tumor regression with IFN-a 2b monotherapy was more than 50%. Here, we reported a patient with advanced HEH, who achieved partial response with the combined therapy of anlotinib and IFN-a 2b. The tumor stayed stable for 2 years with anlotinib monotherapy and regressed obviously 3 months after the combined therapy of anlotinib and IFN-a 2b. The synergistic effect of combined therapy with anlotinib and IFN-a 2b provided a promising guidance for future clinical study.